1978
DOI: 10.1210/endo-103-3-978
|View full text |Cite
|
Sign up to set email alerts
|

Human Parathyroid Hormone: Synthesis and Chemical, Biological, and Immunological Evaluation of the Carboxyl-Terminal Region*

Abstract: The carboxyl-terminal region of human parathyroid hormone (hPTH) was synthesized by the solid phase method. The 32-amino acid fragment, hPTH-(53-84), was prepared for two reasons: 1) to produce antisera directed exclusively against the carboxyl-terminal region of hPTH, which represents the predominant form of the hormone in blood; and 2) to determine whether a portion of the hormone other than the amino-terminal region has any of the biological activity of intact hormone or can bind to PTH receptors. The synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Since most of the calcium regulatory functions could be mapped to the NH2terminal portion (PTH 1-34) of PTH, it was thought that this fragment contains all structural requirements for biological activity of the entire molecule (43,52). The other fragments were regarded as inactive metabolites whose functional importance was confined to processing and intracellular transport events during hormone secretion by the cells of the parathyroid gland (PTH 53-84, references 35,46). However, there is now increasing evidence for a broader spectrum of target tissues, including cartilage (26,33,34), and of hormone action in growth (30,48) and dif-ferentiation processes (8,13) which are mediated by additional functional domains on the mid-regional (23) and COOH-terminal portion (39,40,44) of PTH.…”
mentioning
confidence: 99%
“…Since most of the calcium regulatory functions could be mapped to the NH2terminal portion (PTH 1-34) of PTH, it was thought that this fragment contains all structural requirements for biological activity of the entire molecule (43,52). The other fragments were regarded as inactive metabolites whose functional importance was confined to processing and intracellular transport events during hormone secretion by the cells of the parathyroid gland (PTH 53-84, references 35,46). However, there is now increasing evidence for a broader spectrum of target tissues, including cartilage (26,33,34), and of hormone action in growth (30,48) and dif-ferentiation processes (8,13) which are mediated by additional functional domains on the mid-regional (23) and COOH-terminal portion (39,40,44) of PTH.…”
mentioning
confidence: 99%
“…(12) analyzed the first 34 amino acids; our group analyzed the first 37 amino acids (13) and later completed analysis of the entire molecule (14). The reports by Brewer et aL (12) and Niall et aL (13) (17). In immunoassays using anti-bovine PTH antiserum the synthetic peptide was 4-to 5-fold more reactive than the 53-84 peptide prepared from native human PTH (18).…”
mentioning
confidence: 99%
“…Once these were resolved, it became apparent that, although PTH contains eighty-four amino acids, only the first thirty-four are required for its full biological activity [12] . The function of the remainder of the molecule remains unclear, although some studies have suggested that there may be differential effects of the N-terminal and C-terminal fragments on bone cells [13] and renal tubules [14] .…”
Section: Parathyroid Hormonementioning
confidence: 99%